Islam dan Kosmopolitanisme Budaya - B. Husain, Hamadi (Program Pascasarjana UIN Sunan Ampel Surabaya, 2007)
The Muslim ummah have been dragged into the global culture and have to accept the consequences that emerge thereof. To a certain degree, Muslims were deluded by this global culture and wereâas a resultâshackled into the seemingly irresolvable problems such as the problem of academic objectivity, the ulama-intellectual dichotomy, identity, terrorism, the so-called minor-major paradigm, and the problem of structural poverty. These problems are interdependent and require an allâembracing solution to resolve them. This paper argues that to speak of a solution on the one hand, and to set up the futuristic strategies to deal with those problems on the other, Muslims should first of all build a solid identity. Four steps are required to build this solid identity. (1) Adhering to the Qurâanic morality as the very foundation for Muslimâs way of life. (2) Appropriating to the maximum the human and natural resources available to the Muslims, which would certainly require them to produce the competent scientists, engineers and so on. (3) Applying the rules of syariâah to all aspects of Muslimâs life by first of all gaining a proper understanding about the true teaching of Islam and the real spirit that underlies it. (4) Establishing and maintaining international relationships with foreign countries as well as with other cultures and civilizations. The implication of Islam being a religion of compassion is that it should be built upon understanding and tolerance. Islam advocates the principle of mutual interest and is willing to achieve a better future for all human being.